Never Too Old to Lead: Activating Leadership among Maine’s Older Adults - Crittenden, Jennifer; DeAndrade, Lelia (Maine Policy Review, 2015)
As Maine’s population ages, there will be a growing need to mobilize older Mainers to effect change in their local communities. There are few models available nationally that illustrate how to effectively train and engage baby boomers and older adults as leaders within community contexts. This article examines what is known about leadership development generally and highlights how one program in Maine is training and supporting older leaders who are using volunteer work to improve the health and well-being of their local communities.